European extreme events climate index (E3CI): a climate service for weather induced hazard - Giugliano, Giuseppe; Pugliese, Alessandro; De Vivo, Carmela; Barbato, Giuliana; Ellena, Marta; Tirri, Antonio; Lo Conti, Francesco; Mortini, Laura; Gallo, Ethel; Bonfiglio, Alessandro; Mercogliano, Paola; Rianna, Guido (Frontiers in Climate, 2025)
In recent years, Europe has experienced a notable increase in the frequency and severity of extreme weather events, including heatwaves, floods, droughts, storms, and wildfires. These events have had profound impacts on human life, infrastructure, ecosystems, and economies, highlighting the urgent need to develop effective climate services to prevent, manage and timely respond to associated impacts. The aim of this paper is to describe and validate the European Extreme Climate Index (E3CI), designed as a climate service that allows monitoring the occurrence and severity of extreme weather dynamics across Europe. Starting from data provided by ERA5, the fifth generation of atmospheric reanalyzes produced by the European Center for Medium-Range Weather Forecasts (ECMWF), which covers the entire globe from 1940, E3CI provides insights regarding variations and trends in seven specific dynamics associated with extreme weather events: Extreme Maximum Temperatures, Extreme Minimum Temperatures, Extreme Precipitations, Extreme Winds, Hail, Droughts, and Fires. For each of these, the E3CI collects information at monthly scale in terms of anomalies compared to a reference climatological time span (1981–2010), therefore enabling back-analyses on specific territories, highlighting areas subject to significant weather-induced criticalities. E3CI has proven effective in identifying the spatial distribution and intensity of the extreme precipitation and extreme wind events in the areas affected by powerful storms Dudley, Eunice, and Franklin, as well as the significant heat waves in the summer of 2022 and the extreme precipitation in Emilia Romagna in May 2023. Such index offers numerous application opportunities for businesses, institutions, and communities, in the vein of profound innovation in climate risk management and extreme weather events policies. Its flexible and dynamic nature allows for the production of customizable analysis based on the specific user needs including the ability to refine geographic areas to a radius of approximately 30 km. The data are made available for visualization and download through a dedicated portal, which is updated monthly. Additionally, a Newsletter for subscribers provides information about major events across Europe and their assessment by the corresponding components of E3CI.